The evolution of nursing as a subject in Brazil and Portugal - Carvalho, António Luís (Rev Rene, 2012)
Nursing is a subject that has grown exponentially in terms of number of published articles, as shown by the analysis of data on the SCImago Journal & Country Rank from 2000 to 2010, in which was seen both an exponential increase in the number of documents published by both countries and the rise in the ranking of countries (with the theme "Nursing"), from the 26th to the 6th position in Brazil and from the 47th to the 39th in Portugal. DOI: https://doi.org/10.15253/2175-6783.2012000100001